Development of criteria and indicators for sustainable ecotourism resource management in Penang National Park, Malaysia - Fallah, Marzieh (2014)
The Penang National Park (PNP) is one of the few natural heritage sites located in the northwest corner of Penang Island. It was officially declared a national park in April 2003. The site covers an area of about 1,266 hectares of coastline hills with many exclusive features. With the rapid influx of visitors, PNP is facing several threats of various degrees in ecotourism development, such as poor disposal of solid wastes, flora, and fauna loss, lack of public social involvement or participation and low environmental consciousness among the visitors. Thus, criteria and indicators are effective tools for evaluating and assessing its sustainability. However, up to now, there is still no clear image of the criteria and indicators (C&I) of sustainability index for managing ecotourism in the PNP. Prioritizing C&I set makes it easier for managers to monitor and assess the sustainability of ecotourism management in the park. In terms of time and expenses, the fuzzy model developed for assessing the ecotourism management in the park is a flexible and could easily update the model with new knowledge. The objectives of this study were (1) to identify the important of sustainability C&I for the management of ecotourism in PNP; (2) to develop a hierarchy model of sustainable ecotourism management of PNP through C&I; and (3) to assess the sustainability of ecotourism management in PNP. Methodologically, a panel of 30 academic and non-academic experts in sustainable tourism, ecotourism, and forestry management helped to identify C&I using modified Delphi Technique, and this was followed by conducting the inter-rater reliability (Content Validity Ratio) test. The next step was the application of Fuzzy Analytic Hierarchical Process (FAHP), which is a Multi Criteria Decision Making (MCDM) method through engaging five experts from academic and non-academic fields to prioritize the most important criteria and indicators and to establish the hierarchy model of C&I. Fuzzy Inference System (FIS) was employed in the final step based on certain indicators as inputs by applying Matlab software. The real value, minimum value, and maximum value of each indicator obtained through reports and interview with experts. The membership function of each indicator was established through Matlab software and 169 rules were established for the whole system. A sensitivity analysis was conducted to identify the most effective indicator in determining the sustainability level of the park. In phase one, the modified Delphi technique revealed a consensus of 9 criteria and 21 indicators for the ecotourism management of PNP. The C&I are as follows, ecological dimension (three criteria and six indicators), social dimension (three criteria and seven indicators), economical dimension (two criteria and four indicators), and institutional dimension (one criterion and two indicators). In phase 2, four dimensions of ecological, social, economic, and institutional criteria and indicators were prioritized. In ecological dimension, the criterion of conservation of biodiversity and its sole indicator, the number of threatened species, were found to be the most important criterion and indicator. In the social dimension, the criterion of visitor safety, and its sole indicator, the number of trained, skilled, and dedicated staff in the park were found to be the most important criterion and indicator. In economic dimension, criterion community’s economic improvement, and its sole indicator, number of tourism businesses and services operated and owned by the locals was found to the most important C&I, and in institutional dimension, its sole indicator, number of stakeholders involved in park’s management was the most important indicator. Consistency Ratio (CR) for each pairwise comparison was calculated and it was less than 0.1(< 0.1). The 9 criteria and 21 indicators encompass all the different dimensions of environmental, social, economic and institutional, which were associated with sustainable development concept. In addition, the ecological dimension has the highest priority and institutional cooperation dimension has the lowest priority. An overall sustainability of ecotourism management in PNP indicated that more than 50% was considered medium level of sustainability of the park. In conclusion, this set of C&I would serve as an instrument for monitoring ecotourism activity and evaluating the sustainability of ecotourism management in PNP by the Department of Wildlife and tourism organization in Malaysia. Prioritizing C&I with MCDM ensures that the most important tool in assessing the ecotourism management in PNP and the FIS was used to identify the level and status of sustainability of ecotourism management in the park.